Społeczno-ekonomiczne determinanty zachowań konsumenckich osób starszych w Polsce - Mucha, Monika (2023)
Making purchasing decisions is conditioned by many factors that are still being researched and analyzed. In the case of older people, there are certainly different consumer trends than among younger generations. Takenin this dissertation, the issues are extremely important because they raise the aspect of the broadly understood consumption of older people, which is still an incompletely researched area that requires scientific exploration. Consumption reflects the level of economic development, but also the condition of society, which is why it is constantly analyzed using various methods. The current knowledge on this subject mainly takes into account the impact of economic factors on the consumer behavior of seniors. Over the last decade, attempts have been made to present the phenomenon of consumption among older people, but the vast majority are only theoretical considerations revolving around the mentality of society and economic status. There are no studies that would precisely present the purchasing decisionmaking process of older people, taking into account other issues such as age, household composition and size, health level or general attitudes towards shopping. Any attempts to take these aspects into account are mostly of a pilot nature, and the conclusions obtained do not apply to the entire population of seniors.This doctoral dissertation is an attempt to fill the research gap regarding the importance of selected sociological factors on the consumer behavior of older people. Particular emphasis was placed on consumer roles, the importance of household size, age and access to the sales offer. As it was written earlier, in the literature on the subject, researchers have so far focused on identifying the relationship between income and consumer behavior. There is a lack of research conducted, for example, on the importance of family size on purchasing decisions. It is assumed that older people living alone make purchases in a completely different way than older people living with others. These relationships may be reflected in such key aspects of consumption as the frequency and place of shopping, comparing prices and product features, or the approach to planned and spontaneous purchases. Moreover, due to the size of their household, seniors may assume different roles regarding consumer behavior, which is also important for the proper identification of the issue of seniors' consumption.
Keywords: consumer behavior; seniors; determinants